Christmas Bazaar - British Aid For German Workers
Bemerkungen: [] = Absatzmarken im Volltext des Originals; BRITISH AID FOR GERMAN WORKERS [] (Registered under the War Charity Act 1940) [] It gives us much pleasure to invite you to our [] CHRISTMAS BAZAAR [] to meet [] LADY PAKENHAM [] and other prominent members of the Labour Movement [] at the [] VEGA RESTAURANT [] 56-58 Whitcomb Street, Leicester Square, W.C. 2 [] on Sunday, 12th December, 1948, at 3.30 p.m. [] The large variety of Christmas Presents on sale will include Hand-made Toys and other articles from friends in Germany. [] The whole of the proceeds will be used for our [] CHILDREN'S HOSPITALITY SCHEME [] Please come along, bring your friends and help us to succeed in our effort to give a holiday in this country to as many needy German children as possible. [] Admission charge 2/6, including Coffee & Cake [] Tickets obtainable from Mrs. JENNY FLIESS [] 33 Green Lane, London, N.W. 4 - and at the entrance